Douglas Fairbanks double feature [videorecording (Blu-Ray)] : The three musketeers, The iron mask. - Dumas, Alexandre, 1802-1870; Dumas, Alexandre, 1802-1870; Fairbanks, Douglas, 1883-1939; De La Motte, Marguerite, 1902-1950; Menjou, Adolphe, 1890-1963 (Cohen film collection., 2023)
In THE THREE MUSKETEERS, we are introduced to the young D'Artagnan, a naïve and ambitious farm boy whose acrobatic swordsmanship earns him the respect of King Louis XIII's elite regiment of guards, The Musketeers. Doug reprises his role in THE IRON MASK, which finds D'Artagnan and his fellow Musketeers under threat by the sinister Cardinal Richelieu and Count De Rochefort. THE IRON MASK, King Louis XIII of France is thrilled to have born to him a son - an heir to the throne. But when the queen delivers a twin, Cardinal Richelieu sees the second son as a potential for revolution, and has him sent off to Spain to be raised in secret to ensure a peaceful future for France.